2021
DOI: 10.5897/jpapr2020.0497
|View full text |Cite
|
Sign up to set email alerts
|

Internal control systems and the financial management function in urban governance in Uganda

Abstract: In Uganda like many developing countries, financial management units are facing numerous performance challenges as a result of untold pressure, overwhelming deadlines, limited resources, political patronage and limited professional skills among the practioners. To unravel these impediments, drastic mechanisms need to be put in place to ensure a common balance among all stakeholders; financial resources must be used in a frugal but in a strategic manner to ensure effective and efficient allocation to all sector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…This suggests that there are precise controls, awareness is raised and they are properly implemented. The result is supported by Malowa (2021) which explains a long-lasting evaluation and monitoring framework in public organizations.…”
Section: Very High Existence and Implementationmentioning
confidence: 75%
See 2 more Smart Citations
“…This suggests that there are precise controls, awareness is raised and they are properly implemented. The result is supported by Malowa (2021) which explains a long-lasting evaluation and monitoring framework in public organizations.…”
Section: Very High Existence and Implementationmentioning
confidence: 75%
“…The study found that internal control systems and anti-fraud awareness in inter-governmental organizations have a significant effect on fraud prevention. Furthermore, Malowa (2021) in Uganda, Muhunyo and Jagongo (2018) in Kenya, Oduro (2018) in Ghana and Ujkani and Vokshi (2019) in Kosovo investigated the effect of internal control mechanisms on fraud prevention and implementation of public sector budgetary provisions and found significant effects of control mechanisms in the prevention of misuse of public funds and optimal implementation of public entities' budgetary provisions. However, all these studies are limited in scope because they failed to explore in detail all five components of internal control mechanisms as laid down in the COSO framework.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation